HAK ATAS TANAH ADAT DI SUMENEP: PERALIHAN KEPEMILIKAN DARI KERAJAAN KEPADA SUBYEK HUKUM PERSEORANGAN - Murniati, Sri; Suhartono, Slamet; Sjaifurrachman, Sjaifurrachman (Collegium Studiosum Journal, 2024)
The ownership of Percaton Asta Tinggi land is governed similarly to other types of land ownership. If individual ownership is not recognized, the land is considered state property under the state's full control. This situation reflects a legal vacuum, creating ongoing issues due to the lack of a clear legal framework for ownership and authority over the land. This study examines the management, ownership, status, and authority concerning Percaton Asta Tinggi land. Findings reveal that the land is managed by the Somala Addition Foundation, with control entrusted to the guardians of Asta Tinggi as managers and custodians, as specified by a specific decree. The land is registered under a use-rights certificate, granting the foundation authority to manage the land based on the Regent's Decree. The decree restricts the land's purpose solely for management and benefit utilization, prohibiting personal ownership or sale. While land transfer registrations follow standard procedures, the registration of Percaton Asta Tinggi land is deemed invalid and nullified when intended for sale. This study underscores the need for a legal framework to address the specificities of managing and transferring rights over Percaton Asta Tinggi land.